Tax Debts of Local Budgets: their Scale and Possibility of Cutting - M. A. Pechenskaya (Plekhanov Russian University of Economics, 2019)
The article researches the acute problem of cutting tax debts in the structure of local budgets. The author estimated arrears on payments to the local budget and proposed steps aimed at their cutting. By using economic-statistical methods the article showed the importance of local taxes to municipal bodies' budget and analyzed their dynamics and structure. On the basis of information obtained from the Federal Tax Service and the Federal Treasury the author made the rating of entities and federal districts of the Russian Federation by the rate of debts to the budget growth by local taxes in 2006-2018. The article also investigated the rate of land tax collection in foreign countries. The author systematized the successful Russian and overseas practice of cutting tax debts of local budgets and raising the rate of local taxes collection depending on the level of budget-taxation system (federal, regional, local). The material of the article can be used in the process of teaching students of different stages of education, shaping the research foundation of employees and decision-making on budget and taxation issues on the part of administration bodies.